Tanggung Jawab Negara Terhadap Pengungsi Dan Pengaruhnya Bagi Hubungan Diplomatik, Perspektif Konvensi Wina 1961 - Marlin Paulina Laiyan; Arman Anwar; Lucia Charlota Octovina Tahamata (Faculty of Law, Universitas Pattimura, 2023)
Introduction: The Afghan government's pro-Western policies and secular ideologies caused a strong reaction from radical groups who wanted to establish a new Afghan government, resulting in a civil war in Afghanistan.Purposes of the Research: The purpose of this study is to examine and discuss the implementation of state responsibilities and their impact on Afghan refugees in Indonesia for diplomatic relations, from the perspective of the 1961 Vienna Convention.Methods of the Research: This research is based on the normative legal research method which is also known as library research. The approach used is a conceptual approach, a statutory approach, and a case approach. The procedure for collecting legal materials is carried out by studying and analyzing library materials in relation to literature, conventions, and laws. Processing and analysis of legal materials is carried out by examining, researching, and compiling legal materials in an orderly and logical manner to ensure the completeness of legal materials so that they can be interpreted.Results of the Research: Based on the results of research on state responsibility for refugees and its effect on diplomatic relations, the perspective of the 1961 Vienna Convention. The principle of state sovereignty in international relations has a very large influence on the right of a country to control a government territory, society or over itself so that in practice it is against refugees a state is negligent or violates what is required by international law, namely in providing protection, promotion and respect for human rights based on a treaty and customary international law. As an example; there are several countries that are parties to the 1951 Convention, act to receive and provide protection, expel and return refugees to other places or to their countries of origin where these actions have violated the Non-Refoulement Principle Article 33 paragraph 3 which is basically related to the principle of protecting human rights. Meanwhile, there are also countries that, although not participants in the 1951 Convention, accept and make laws and regulations that apply to refugees to ensure the protection of human rights that refugees do not get because of conflicts that occur in their place or country of origin.